Study guides

☆☆

Q: 2 3 plus 4 6

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

1 + 2 = 3 + 3= 6 + 4 = 10 + 5 = 15 + 6 = 21 +7 = 28 + 8 = 36 + 9 = 45

4x + 2 +2x - 6 = 0 6x -4 = 0 +4 +4 6x=4 x= 4/6 x=2/3

21, sigh.

Multiply out the factors and then you can check: (x + 2)(x + 3) = x² + 3x + 2x + 6 = x² + 5x + 6 ≠ x² + 3x + 4 Therefore False.

(10 + 1) x 10/2

Related questions

-6=-6(-a+2)+3(a-4)

2 + 3 + 4 + 5 + 6 = 20

9 + 9 + 9 + 9 + 9 + 9 + 6 + 6 + 6 + 6 + 2 + 2 + 23 + 3 + 3 + 4 + 4 + 4 = 123

6+4+3=2 when it is a mistake

3 + 4 + 2 + 8 + 6 + 0.3 + 4 + 2 + 8 + 6 + 0.3 + 4 + 2 = 49.6

(2-3)+(4-6)=-3

2+4+(-3)+(-4) 2+4=6 6+(-3)+(-4)=-1 -3+-4=-7 or 2+4+(-3)+4-4 2+4=6 4-4=0 +(-3)=-3 6-3=3

-3 + 4 - 6 + 3 - 2 + 42 = 1 - 6 + 3 - 2 + 42 = - 5 + 3 - 2 + 42 = - 2 - 2 + 42 = - 4 + 42 = 38

2/3 +4/6 =

2 + 3 - 4 + 7 = -6

10

4/6 = 2/3; therefore, 2/3 + 4/6 = 4/3.

People also asked